Talcott Parsons' AGIL Perspective Learning Strategy in the Independent Curriculum: A Systematic Literature Review - Fitria Ningsih; Gita Aryani; Nia Kurnia; Salfen Hasri; Irawati Irawati (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
The implementation of the Independent Curriculum marks a paradigm shift in education that positions schools as complex social systems, not merely technical classroom learning spaces. This curriculum demands learning flexibility, differentiation, and the strengthening of teachers' professional autonomy in designing contextual and student-centered learning strategies. However, various studies indicate a gap between the design of the Independent Curriculum policy and its implementation practices in schools, characterized by limited teacher adaptive capacity, high administrative burdens, and weak structural support in teaching staff management. These conditions indicate that the problems of implementing the Independent Curriculum are not solely related to individual teacher competencies, but also to how the education system manages the role of teachers, the school's organizational structure, and work culture in an integrated manner. This article aims to analyze and synthesize learning strategies in the implementation of the Independent Curriculum from the perspective of Talcott Parsons' social systems theory through the AGIL (Adaptation, Goal Attainment, Integration, and Latency) framework. This study employed a qualitative approach using the Systematic Literature Review (SLR) method for scientific journal articles indexed by Google Scholar and relevant to the topics of the Independent Curriculum, learning strategies, teacher management, and AGIL theory. The study's findings indicate that learning strategies serve as a systemic mechanism linking curriculum policies with learning practices and determining the balance between adaptation, goal achievement, social integration, and value preservation within the education system.